Concussion knowledge and return-to-play attitudes among subelite rugby union players - Walker, S (South African Journal of Sports Medicine, 2015)
Background. Concussion is a significant health issue in rugby union. However, little is known about players’ levels of concussion knowledge or return-to-play (RTP) attitudes. Objectives. To determine the concussion knowledge and concussion-related RTP attitudes of subelite rugby union players in South Africa. Methods. Subelite rugby union players (n=127; mean age 24.1 years) completed a measure of concussion knowledge and a concussionrelated RTP attitude scale. Frequencies were calculated with regard to concussion knowledge and RTP attitudes for the total sample, as well as separately for previously concussed and non-concussed participants. Pearson’s χ2 tests and t-tests for independent groups were employed to determine significant differences in concussion knowledge and RTP attitudes between previously concussed and nonconcussed participants. Results. Participants displayed varying, yet generally less than optimal levels of concussion knowledge. Knowledge of concussion-related RTP protocols (20 - 23%) and the efficacy of safety equipment (20 - 25%) was particularly poor. The subelite rugby players included in the sample did not hold notably conservative RTP attitudes, with the majority expressing a willingness to participate in practice (74%) and competition (47 - 56%) without having fully recovered from a concussion. No significant differences were apparent with regard to the RTP attitudes and concussion knowledge of the previously concussed and non-concussed players. Conclusion. The general level of concussion knowledge among subelite rugby union players appears less than optimal. Moreover, the majority of these players expressed an intention to RTP before they had fully recovered from concussion.